A dynamic DNA nanosponge for triggered amplification of gene-photodynamic modulation. Issue 18 (28th March 2022) - Luo, Dan; Lin, Xue; Zhao, Yun; Hu, Jialing; Mo, Fengye; Song, Gege; Zou, Zhiqiao; Wang, Fuan; Liu, Xiaoqing
Abstract : Oligonucleotide drug delivery approach is provided with a biomimetic, dynamic DNA nanomaterial, which enables disease gene regulation and auxiliary therapy in a controllable and self-boosting manner. Abstract : Nucleic acid therapeutics has reached clinical utility through modulating gene expression. As a potential oligonucleotide drug, DNAzyme has RNA-cleaving activity for gene silencing, but faces challenges due to the lack of a safe and effective delivery vehicle and low in vivo catalytic activity. Here we describe DNAzyme-mediated gene regulation using dynamic DNA nanomaterials with intrinsic biocompatibility, stability, tumor-targeted delivery and uptake, and self-enhanced efficacy. We assemble programmable DNA nanosponges to package and deliver diverse nucleic acid drugs and therapeutic agents such as aptamer, DNAzyme and its cofactor precursor, and photosensitizer in one pot through the rolling circle amplification reaction, formulating a controllable nanomedicine using encoded instructions. Upon environmental stimuli, DNAzyme activity increases and RNA cleavage accelerates by a supplementary catalytic cofactor. In addition, this approach induces elevated O2 and 1 O2 generation as auxiliary treatment, achieving simultaneously self-enhanced gene-photodynamic cancer therapy. These findings may advance the clinical trial of oligonucleotide drugs as tools for gene modulation.